Nanotubular Aluminosilicates: A Case Study for Science and Industry - Escudey-Castro, A; Escudey-Castro, A; Arancibia-Miranda, N; Arancibia-Miranda, N; Lillo-Vidal, S (Sociedad Chilena de Quimica, 2013)
The renewed interest in imogolite nanotubes, with structural similarities with carbon nanotubes (CNTs), has led to a new search of the potential of imogolite in the field of nanoscience. The applications of imogolite started being studied at the beginning of the 1970s, but the lack of technological development prevented a detailed study of this aluminosilicate. Furthermore, the strong incursion CNTs, which show exceptional structural characteristics and physical properties, left imogolite as the subject of secondary studies and applications in nanotechnology. This review, revise the scientific interest on imogolite from its discovery until the present, showing the main areas of research and development for this nanotube from a nanotechnological point of view.